6 Characteristics of thunderstorm asthma EMS attendances in victoria, australia. (21st May 2017) - Andrew, E; Nehme, Z; Bernard, S; Smith, K
Abstract : Aim: Thunderstorm Asthma (TA) occurs when a dangerous mix of pollen and severe weather trigger acute respiratory distress symptoms in people with allergic rhinitis and asthma. We sought to describe the characteristics of patients attended by emergency medical services (EMS) during the largest global epidemic of TA which occurred in Melbourne on 21/11/2016. Methods: A retrospective observational study of electronic EMS patient care records was conducted for all cases occurring during TA, between 1800hrs on 21/11/2016 and 2359 hours on 22/11/2016 (30 hours). Results were compared with a standard comparator period defined as the seven days prior to the event (14/11/2016 to 20/11/2016). Results: EMS responded to 3631 cases during the TA event, compared with an average of 2419 cases per 30 hours during the comparator period. During TA, the final paramedic diagnosis was acute respiratory distress in 28.3% of patients (Asthma=18.0%, Shortness of Breath=10.3%), compared with 3.6% of patients during the comparator period (Asthma=0.6%, Shortness of Breath=3.0%, p<0.001). Whilst there was an absolute increase in the number of time-critical cases, the proportion of acute respiratory illness patients considered time-critical after initial paramedic assessment remained stable between the two periods (42.0% vs. 43.5%, p=0.6). However, a 50% increase in the rate of out-of-hospital cardiac arrest was observed during TA. In the cohort of Asthma patients, 74.9% reported a history of asthma during TA compared with 91.1% during the comparator period (p=0.006). The most common paramedic intervention for patients with acute respiratory distress was administration of salbutamol (72.5%) while 8.0% of patients received adrenaline. Conclusion: The TA event in Melbourne was associated with a significant increase in EMS attendances to patients with acute respiratory illnesses and cardiac arrest. Conflict of interest: None declared. Funding: None declared.